Signaling by the TNFR superfamily in B-cell biology and disease - Rickert, Robert C. (2011)
Members of the tumor necrosis factor receptor superfamily (TNFRSF) participate prominently in B-cell maturation and function. In particular, B-cell activating factor belonging to the TNFR family receptor (BAFF-R), B-cell maturation antigen (BCMA), and transmembrane activator and calcium modulator and cyclophilin ligand interactor (TACI) play critical roles in promoting B-cell survival at distinct stages of development by engaging a proliferation-inducing ligand (APRIL) and/or BAFF. CD40 is also essential for directing the humoral response to T-cell-dependent antigens. Signaling by the TNFRSF is mediated primarily, albeit not exclusively, via the TNFR-associated factor (TRAF) proteins and activation of the canonical and/or noncanonical nuclear factor-κB (NF-κB) pathways. Dysregulated signaling by TNFRSF members can promote B-cell survival and proliferation, causing autoimmunity and neoplasia. In this review, we present a current understanding of the functions of and distinctions between APRIL/BAFF signaling by their respective receptors expressed on particular B-cell subsets. These findings are compared and contrasted with CD40 signaling, which employs similar signaling conduits to achieve distinct cellular outcomes in the context of the germinal center response. We also underscore how new findings and conceptual insights in TNFRSF signaling are facilitating the understanding of B-cell malignancies and autoimmune diseases.